hFcγRIIa: a double-edged sword in osteoclastogenesis and bone balance in transgenic mice - Miao, Jie; Wang, Hong-Min; Pan, Xiao-Hua; Gong, Zheng; Gao, Xiao-Ming; Gong, Fang-Yuan (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) is a chronic autoimmune disease accompanied by local and systemic bone loss. FcγRs, especially FcγRIIa (hFcγRIIa), have been implicated in the pathogenesis of RA. However, the contribution of hFcγRIIa to bone loss has not been fully elucidated. In the present study, we demonstrated the double-edged sword role of hFcγRIIa on osteoclast differentiation through investigations involving hFcγRIIa-transgenic (hFcγRIIa-Tg) mice. Our findings reveal that hFcγRIIa-Tg mice, previously shown to exhibit heightened susceptibility to collagen-induced arthritis (CIA), displayed increased osteoporosis during CIA or at advanced ages (40 weeks), accompanied by heightened in vivo osteoclast differentiation. Notably, bone marrow cells from hFcγRIIa-Tg mice exhibited enhanced efficiency in differentiating into osteoclasts and bone resorption in vitro compared to wild-type mice when stimulated with receptor activators of NF-κB ligand (RANKL). Additionally, hFcγRIIa-Tg mice exhibited augmented sensitivity to RANKL-induced bone loss in vivo, highlighting the osteoclast-promoting role of hFcγRIIa. Mechanistically, bone marrow cells from hFcγRIIa-Tg mice displayed heightened Syk self-activation, leading to mTOR-pS6 pathway activation, thereby promoting RANKL-driven osteoclast differentiation. Intriguingly, while hFcγRIIa crosslinking hindered RANKL-induced osteoclast differentiation, it activated the kinase cAbl, subsequently triggering STAT5 activation and inhibiting the expression of osteoclast-associated genes. This study provides novel insights into hFcγRIIa-mediated osteoclast biology, suggesting promising therapeutic targets for managing bone remodeling disorders.